EFFECT OF TEMPERATURE NONUNIFORMITY ON HEAT TRANSFER IN AN UNSHROUDED TRANSONIC HP TURBINE: AN EXPERIMENTAL AND COMPUTATIONAL INVESTIGATION - Qureshi, I; Smitht, A; Chana, K; Povey, T; ASME (2010)
Detailed experimental measurements have been performed to understand the effects of turbine inlet temperature distortion (hot-streaks) on the heat transfer and aerodynamic characteristics of a full-scale unshrouded high pressure turbine stage at flow conditions that are representative of those found in a modern gas turbine engine. To investigate hot-streak migration, the experimental measurements are complemented by three-dimensional steady and unsteady CFD simulations of the turbine stage. This paper presents the time-averaged measurements and computational predictions of rotor blade surface and rotor casing heat transfer. Experimental measurements obtained with and without inlet temperature distortion are compared. Time-mean experimental measurements of rotor casing static pressure are also presented. CFD simulations have been conducted using the Rolls-Royce code Hydra, and are compared to the experimental results. The test turbine was the unshrouded MT1 turbine, installed in the Turbine Test Facility (previously called Isentropic Light Piston Facility) at QinetiQ, Farnborough UK. This is a short duration transonic facility, which simulates engine representative M, Re, √, and T g/Twat the turbine inlet. The facility has recently been upgraded to incorporate an advanced second-generation temperature distortion generator, capable of simulating well-defined, aggressive temperature distortion both in the radial and circumferential directions, at the turbine inlet. Copyright © 2010 by ASME.